Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2020)
A dataset containing 805498 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is one of (Eleocharis geniculata (L.) Roem. & Schult., Picea glauca (Moench) Voss, Antennaria alpina (L.) Gaertn., Solidago speciosa Nutt., Vitis labrusca L., Rubus cuneifolius Pursh, Prunus serotina Ehrh., Symphoricarpos orbiculatus Moench, Adlumia fungosa (Aiton) Greene ex Britton, Stern & Poggenb., Physalis lanceolata Michx., Trianthema portulacastrum L., Lycopodiella inundata (L.) Holub, Schizachyrium scoparium (Michx.) Nash, Drymaria cordata (L.) Willd. ex Schult., Ophioglossum petiolatum Hook., Symplocos tinctoria (L.) L'Hér., Dendrolycopodium obscurum (L.) A.Haines, Polygonatum biflorum (Walter) Elliott, Oxalis corniculata L., Menyanthes trifoliata L., Magnolia acuminata (L.) L., Poa nemoralis L., Cocculus carolinus (L.) DC., Pellaea atropurpurea (L.) Link, Verbena urticifolia L., Ophioglossum vulgatum L., Xerophyllum asphodeloides (L.) Nutt., Sparganium emersum Rehmann, Cunila origanoides (L.) Britton, Lycopus virginicus L.)", "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 805498 records from 1367 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0081983-200613084148143/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences